Manipulating propagating graphene plasmons at near field by shaped graphene nano-vacancies - Du, Luping (2014)
Surface plasmons in graphene have many promising properties, such as high confinement, low losses, and gate-tunability. However, it is also the high confinement that makes them difficult to excite due to their large momentum mismatch with free-space mid-infrared light. We propose to use shaped graphene nano-vacancies to compensate for the momentum mismatch, revealing its high flexibility in graphene plasmon (GP) excitation and manipulation. We first examine the electromagnetic standing waves generated with a pair of straight vacancies, in order to verify the excitation of GPs and to illustrate their tunability with gate voltage. Plasmonic lenses are then designed to achieve the super-focusing of mid-infrared light and to generate plasmonic vortices in graphene. A∼0.0125λ0 hotspot is generated, far below the optical diffraction limit, hence revealing the capability of light control at deep-subwavelength scale.